A novel and efficient bilateral remote user authentication scheme using smart cards - Pathan, Al-Sakib Khan; Hong, Choong Seon; Suda, Tatsuya (2007)
This paper proposes a novel remote user authentication scheme using smart cards which allows both the authentication server (AS) and the user to verify each other’s authenticity. Our scheme is efficient enough to resist the known attacks that could be launched against remote user authentication process.